Anti Klimaks Implementasi E-Government: Analisis Partisipasi Masyarakat Petani Di Kabupaten Gunungkidul - Wicaksono, Ferri (Fakultas Ilmu Administrasi Universitas Dr. Soetomo, 2018)
This research is located in Gunungkidul Regency, Yogyakarta Special Region (DIY). The rapid development of global information technology has driven a paradigm shift in society towards the era of digital society. This fact directs the massive use of electronic media in the public service bureaucracy in Indonesia. In order to realize a clean, transparent public service and be able to answer the demands of change effectively, in line with Presidential Instruction No. 3 of 2003. Dilemma when the Gunungkidul Regency Government is seeking e-government as a reform of the public service bureaucracy that is intended for the community as the recipient of service benefits, there are elements of farmer communities that tend to be difficult to adopt new technologies. The Gunungkidul Regency Government has consistently developed a website up to the sub-district level totaling 18 sub-districts and village levels totaling 144 villages with domains namely